(untitled) (Journal of the College of Education for Women, 2019)
Victorian age is known as a time of perpetual change. It is a time of new industrialization, increased urbanization and new technology. Therefore, one of the strongest undercurrents of this is the position of women. Woman at that time was viewed as “an angel in the house” especially this who belongs to the upper-middle class. She is described in such term because she spends much time in her domestic domain. Therefore, she should be passive, obedient and dependent. Despite the Victorian society contains several classes; women are defined under two labels: the angel and the demon or the whore. The angel woman can be any woman from the lower middle class to the aristocracy, while the whore refers to any working class woman. The difference between the two is that the second type has to work outside to earn the living. Living in a patriarchal society, both types of women are oppressed. The first type, the angel, should not have the right to be independent or even to make any choice and if she does, she will be mad, dangerous and demon, while the second type is considered rebellious and whore for being seen among the outsiders. Thus and as result, both of them are mistreated as outcasts. The Pre-Raphaelite writers are daring and so interested in the issue of woman because of the reasons mentioned above. One of them is Mary Elizabeth Braddon. In her novel, Lady Audley’s Secret, she tries to show the position of women and the Victorian attitudes towards them through the symbol of the characters especially the female characters. There are no much details about them in the novel because they are used as symbol to bring the attention of the readers to social and moral problems concerning the Age. This can be clearly seen in the character of Lady Audley. She stands for the threatening woman who tries to make a change in a patriarchal world. The female characters in the novel represent the fear of women’s independence. Lady Audley is considered a devilish and dangerous woman and should be buried alive in an asylum because she violates the prevailing traditions. She portrays the fears of many people in the patriarchal society including even the women as Alicia, Phoebe, and Clara. Lady Audley shows that even those women, who are obedient, are oppressed by the severe society. They are the victims of the filial and marital power. Concerning classes, Lady Audley shows that it is a crime for the lower class to intrude high class. They are considered criminal and deserve punishment while the high class has the authority to do anything. Because Lady Audly intrudes the upper class by marrying Sir Michael, she is considered a criminal. Lady Audly is not a mere character. She is a new heroine and representative because she stands for all female characters who try to make changes in a patriarchalworld.